Understanding Teacher Code Switching and Mixing in English Instruction: Memahami Alih Kode dan Campur Kode Guru dalam Pengajaran Bahasa Inggris - Setyawan, Sekar Ayu Gaby Safitri; Mandarani, Vidya (Indonesian Journal of Education Methods Development, 2024)
General Background: The phenomenon of code switching and code mixing in bilingual education contexts has garnered attention for its role in facilitating communication and comprehension. Specific Background: While the use of these linguistic strategies is acknowledged in language teaching, there is limited research focusing specifically on their application by teachers during English language instruction. Knowledge Gap: Existing studies often overlook the practical implications of code switching and mixing in the classroom setting, particularly regarding teachers' motivations and the types employed. Aims: This study aims to analyze the implementation of code switching and code mixing by teachers in English learning environments and to understand the underlying reasons for their usage. Results: Employing a qualitative research method, data were collected through direct classroom observations and interviews with a teacher. The findings reveal that teachers utilized all recognized types of code switching and mixing, primarily to enhance student understanding of the material and to ensure the achievement of learning objectives. Novelty: This research contributes to the existing literature by providing empirical evidence of the strategies employed by teachers in real classroom settings. Implications: The insights gained from this study underscore the significance of code switching and mixing as effective pedagogical tools, suggesting that educators can leverage these strategies to improve student comprehension and engagement in English language learning. Highlights: Comprehensive Use: Teachers employed all types of code switching and mixing as per theoretical frameworks. Enhancing Understanding: The primary motivation for using these strategies was to improve student comprehension of the material. Effective Pedagogical Tool: Code switching and mixing are recognized as valuable techniques for achieving learning objectives in language instruction. Keywords: code switching, code mixing, English learning, teacher strategies, classroom interaction.